2022
DOI: 10.1016/j.psj.2021.101557
|View full text |Cite
|
Sign up to set email alerts
|

MiR-29b-1-5p regulates the proliferation and differentiation of chicken primary myoblasts and analysis of its effective targets

Abstract: Several recent studies investigated the role of the miR-29 family in muscle development. However, only a few studies focused on chicken skeletal muscle. In the present study, cell cycle, 5-ethynyl-2’-deoxyuridine ( EdU ), cell counting kit-8 ( CCK-8 ), and other assays indicated that miR-29b-1-5p can inhibit the proliferation of chicken primary myoblasts ( CPMs ); the western blot assay and immunofluorescence detection of MYHC demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…A E12: gga-miR-130b-5p target genes; B E16: gga-miR-1643-5p target genes; C E19: gga-miR-12218-5p target genes; D E21: gga-miR-132b-5p target genes gga-miRNA-454-3p does not affect primary myoblast differentiation, it inhibits differentiation by targeting the myotube-associated protein SBF2 [27]. A study focused on the chicken skeletal muscle indicated that miR-29b-1-5p inhibits the proliferation of chicken primary myoblasts and promotes the differentiation of myoblasts via an effective target gene, ANKRD9 [28]. Meanwhile, miR-29b-1-5p and miR-133a-5p are sponges for circFGFR2 in skeletal muscle proliferation and differentiation [29].…”
Section: Discussionmentioning
confidence: 99%
“…A E12: gga-miR-130b-5p target genes; B E16: gga-miR-1643-5p target genes; C E19: gga-miR-12218-5p target genes; D E21: gga-miR-132b-5p target genes gga-miRNA-454-3p does not affect primary myoblast differentiation, it inhibits differentiation by targeting the myotube-associated protein SBF2 [27]. A study focused on the chicken skeletal muscle indicated that miR-29b-1-5p inhibits the proliferation of chicken primary myoblasts and promotes the differentiation of myoblasts via an effective target gene, ANKRD9 [28]. Meanwhile, miR-29b-1-5p and miR-133a-5p are sponges for circFGFR2 in skeletal muscle proliferation and differentiation [29].…”
Section: Discussionmentioning
confidence: 99%
“…For example, muscle phosphofructo-1 kinase ( PFKM ) is a key regulatory enzyme of glycolysis ( Garcia et al, 2009 ), and regulates the insulin-stimulated glycolytic pathway in chicken skeletal muscle ( Seki et al, 2006 ). Lactate dehydrogenase A ( LDHA ) inhibits the proliferation and promotes differentiation of chicken primary myoblasts through being targeted by miR-29b-1-5p ( Li et al, 2022 ). Studies have pointed out that white streaks and lignified chicken breasts in broiler breasts may be related to LDHA , but no causal relationship has been established ( Malila et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…CPMs were isolated from the leg muscles of E11 AA broiler following previously described methods ( Cai et al, 2018 ; Li et al, 2022 ; Wei et al, 2022 ). Each in vitro cell experiment was isolated and cultured from at least 10 E11 AA broiler leg muscles.…”
Section: Methodsmentioning
confidence: 99%
“…After the cells were overgrown, they were used for subsequent experiments. For the construction of the differentiation model of CPMs ( Cai et al, 2018 ; Li et al, 2022 ), the cells were collected by observing the cell fusion degree at 50 and 100% (labeled as G1 and G2). In addition, when the cells were confluent to 90 to 95%, the differentiation medium containing 2% horse serum (Vivacell, Shanghai, China)14 and 1% penicillin/streptomycin (Solarbio, Beijing, China) was used for further culture.…”
Section: Methodsmentioning
confidence: 99%